Improving Integrally Heated Composite Tooling Through Cold Sprayed Copper Coatings and Heat Transfer Simulations - Baril-Gosselin, Simon (Université d'Ottawa / University of Ottawa, 2013)
Integrally heated composite tooling (IHCT) is seen as a low cost alternative to autoclave manufacturing of polymer matrix composites (PMCs). IHCTs consist of a composite tool heated by surface heaters; temperature distribution is ensured by a thermally conductive metallic layer. The main original contributions of this thesis was the development of a new method for applying copper coatings onto carbon fibre/epoxy PMCs using pulsed gas dynamic spraying, the production of larger size samples, and the characterisation of the performance of the coatings and laminates obtained. It was shown that this method has potential for producing the thermally conductive layer in an IHCT. Another contribution was the characterisation of parameters affecting temperature distribution across IHCTs through heat transfer simulations, leading to guidelines for IHCT design.
Keywords: Composite; Cold spray; Pulsed gas dynamic spraying; Composite tooling; Manufacturing